Secured indoor powerline communication using CDMA technique - AbuElHassan, Mohamed Sherfi Omer; Ngah, Razali (2007)
With the rapid growth of home networks, there is an ongoing need for an economical and reliable communications system that can be implemented in any building. Powerline channel has been considered as a medium not only for low-rate, control communications, but also for high-speed data communications, such as home networking and Internet access. Communication over the power line has become an opportunity for the power distributors to implement new services. The focus of this paper is to address the challenges in PLC such as noise and security. The techniques to overcome these challenges are presented.